Wideband slot‐loaded dipole for base station antenna element. Issue 12 (December 2014) - Yang, Wenxia; Wong, Hang
ABSTRACT A low‐profile wideband unidirectional dipole antenna with L‐shaped slots loaded is presented. The antenna is simply excited by a 50 Ω coaxial cable on the dipole. A wide impedance bandwidth of 54% (|S11| < −10 dB) from the frequency of 1.57–2.74 GHz is achieved. Stable radiation pattern with low cross‐polarization, nearly identical E‐ and H‐plane patterns is observed over the entire operating frequency band. The average gain of the antenna is about 8.5 dBi over the frequency range 1.7–2.7 GHz. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2933–2937, 2014